2014
DOI: 10.12703/p6-70
|View full text |Cite
|
Sign up to set email alerts
|

Advances in the management of cutaneous squamous cell carcinoma

Abstract: Cutaneous squamous cell carcinoma is one of the most common non-melanoma skin cancers worldwide. While most cutaneous squamous cell carcinomas are easily managed, there is a high-risk subset of tumors that can cause severe morbidity and mortality. Tumor characteristics as well as patient characteristics contribute to the classification of cutaneous squamous cell carcinomas as low-risk vs. high-risk. Advances in the treatment of cutaneous squamous cell carcinomas largely relate to the management of this high-ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0
7

Year Published

2015
2015
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 68 publications
0
36
0
7
Order By: Relevance
“…In contrast, the treatment algorithm for SCCs is more established, with either surgery or radiotherapy used as first-line treatment, followed by adjuvant chemotherapy, molecular therapy or additional radiotherapy depending on staging 26. Misdiagnosing MPTT as SCC could alter management and prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the treatment algorithm for SCCs is more established, with either surgery or radiotherapy used as first-line treatment, followed by adjuvant chemotherapy, molecular therapy or additional radiotherapy depending on staging 26. Misdiagnosing MPTT as SCC could alter management and prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…2 Most patients with cSCC will have a good prognosis if the lesion is completely excised by surgery; however, there is a subsection (about 4%) of lesions that metastasize, and 1.5% of patients will die from the disease. 2,3 Brunner et al reported that of 603 patients with metastatic cSCC, 89% of patients with distant metastasis died within 5 years. 4 Hence, other effective treatments are also necessary for cSCC.…”
Section: Introductionmentioning
confidence: 99%
“…5 However, it carries a number of adverse effects such as soft-tissue necrosis, epidermal atrophy and radiation-induced malignancy, which some patients with cSCC may not be able to tolerate. 3 Chemotherapy is another frequently used method for the treatment of metastatic cSCC, and includes drugs such as cisplatin, bleomycin, doxorubicin and methotrexate, alone or combined with 5-fluorouracil. 6,7 However, the results are inconsistent and an effective chemotherapeutic method is still lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Wegen der hohen Strahlensensitivität des cSCC kann diese Therapiemodalität für Patienten in Betracht gezogen werden, die für eine operative Behandlung nicht infrage kommen, sowie für Patienten mit lokal fortgeschrittener Erkrankung oder in Situationen, in denen eine Exzision mit anschließender Rekonstruktion kosmetisch/funktionell inakzeptabel ist. Darüber hinaus ist eine Strahlentherapie mit adjuvanter Zielsetzung häufig in Fällen indiziert, in denen die Tumorränder positiv sind, sowie bei Vorliegen einer perineuralen Invasion oder Beteiligung benachbarter Strukturen oder bei Rezidiven [4]. …”
Section: Einführungunclassified